Body composition, anthropometric parameters, and starting age make a difference between elite lead climbers and boulderers - a retrospective study - Ginszt, A.; Zielinski, G.; Bys, A.; Zieba, E.; Zaborek, M.; Lyczba, J.; Gawda, P.; Ginszt, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Previous research studies suggest that the success of the sport climber is primarily determined by variables that can be improved through training, such as strength, power, or endurance, rather than anthropometric variables. However, there is a lack of research assessing differences in body composition and anthropometric parameters between the two most common sport climbing sub-disciplines - lead climbing and bouldering. METHODS: This study analyzed the relationships between age, climbing experience, body mass, body height, and body mass index, and the best result in sport climbing among male lead climbers and boulderers. The data of the 422 best male sport climbers based on 8a.nu world ranking were an-alyzed in two categories: "Route Ranking: Top-10 climbs last 12 months" for lead climbers and "Boulder Ranking: Top-10 climbs last 12 months" for boulderers. RESULTS: The comparison of the lead climbers and boulderers (collectively, in groups Elite and Higher Elite) showed that the lead climbers started climbing at a younger age, had a lower body mass and lower height, and had a longer period to achieve the hardest route in comparison with the boulderers. Lower height and lower body mass were also observed among "Higher Elite" lead climbers compared to "Elite" lead climbers. When comparing the "Elite" and "Higher Elite" groups in both lead climbing and bouldering, the "Higher Elite" group started climbing at a younger age and had a longer period to achieve the hardest route. CONCLUSION: This retrospective study suggests that lower body mass and height are more crucial for lead climbing performance than for bouldering. Younger starting age and longer sporting experience are the key points in the "Higher Elite" level in both subdisciplines.